PELAYANAN KESEHATAN DAN VAKSINASI SE TERHADAP SAPI BALI DI DESA BELOK SIDAN, KECAMATAN PETANG, KABUPATEN BADUNG - MADE SUMA ANTHARA (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2008)
ABSTRACT This community service aimed to improve the cattle health and immunity to protect them from Septicemia epizootica (SE) disease. Animal health service with anthelmintics and SE vaccination program on bali cattle were done at Belok Sidan village, county of Petang, Badung regency on Thursday, October 4th , 2007. The service is conducted by gathering farmers (cattle owner). There were 34 farmers with 66 cattles. Team examined animal's health, give treatment unhealth animal and free consultation about animal's health. The health animals were vaccinated with SE vaccines. From total 66 cattles, 33 cattles were given SE vaccine, 31 cattles were treated with vitamine B-complex, 5 cattles were orrally given anthelmintics and 5 cattles were treated with antibiotic. All of cattles were sprayed with insect repellent. All farmers were interest with this program and hope contiunue for next time.